Evaluating the Implementation of the Training Needs Assessment Policy at Imam Muhammad ibn Saud Islamic University - Alharbi, Dalia Abdulaziz; Alhijji, Alaa Ibrahim; Alharthi, Manal Trekhem; AlRakban, AlJawhrah Othman (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify the extent to which the policy of training needs assessment is implemented for the staff of Imam Muhammad ibn Saud Islamic University. The researchers employed the descriptive survey methodology, and the study tool was a questionnaire consisting of ten statements under a single dimension. It was applied to a purposive sample of 20 administrative staff members at the university. The results indicated that the study participants were neutral in their agreement regarding the level of implementation of the training needs assessment policy at the university, with a mean score of 3.32 out of 5. The highest-rated statements in terms of agreement were: the presence of clear standards and regulations adhered to by the training administration; diversity in training fields addressed in the needs assessment; and the identification of current and future training needs in alignment with the university’s strategic vision, training needs analysis, and annual performance evaluations. Based on the findings, the researchers recommended placing greater emphasis on conducting regular training needs assessments for the university’s staff, providing clear and specific mechanisms such as templates to identify training needs, and developing an annual training plan based on the results of the training needs assessments for the staff of Imam Muhammad ibn Saud Islamic University.
Keywords: Training needs; Imam Muhammad ibn Saud Islamic University; Saudi Arabia